The Development of Participatory Energy Conservation Promotion in Designated Chemical Industrial Factories - Somvadee, Kittiwat; Chankoson, Thitinan; Triwong, Peeteenut (Asian Administration and Management Review, 2019)
The objectives of this study were 1) to analyze the key components of the participatory energy conservation promotion in designated chemical industrial factories and 2) to develop a model of participatory energy conservation promotion in designated chemical industrial factories. The population was comprised of the executives and employees in designated chemical industrial factories. The mixed-method research approach integrating quantitative and qualitative methods was adopted in the present research. The research instruments were the semi-structured interview sheet and questionnaire. The data were analyzed using the content analysis technique, the statistical analysis of frequency, percentage, mean, and standard deviation, and the exploratory factor analysis method. The results from the exploratory factor analysis were used to develop the model of participatory energy conservation promotion. The developed model was reviewed through the focus group discussion with 12 experts in order to confirm its validity and completeness. The results suggested that the model of participatory energy conservation promotion in designated chemical industrial factories consisted of 9 components of internal factors, called SENSATIONS2: 1) Synergy, 2) Encouraging leadership, 3) Know, 4) Strategy, 5) Attribute, 6) Technique, 7) Improvement, 8) Organization, and 9) Numerical chemistry, and 2 components of external factors: 1) Standardization and 2) Stakeholders.